(untitled) (El Hilo de la Fabula, 2015)
The paper takes into account the short stories by Hebe Uhart published in the collections Del cielo a casa (2003) and Turistas (2008). The study analyzes how she decentralises writing through the appropriation and the de−construction of mechanisms related to travel reportage. By doing so, Hebe Uhart advances a more complex interpretation of tourist travel as a form of displacement which involves the twofold experience of both alienation and self−alienation